Endocrine complications during and after adolescence in a patient with cystinosis - Moon Bae Ahn; Sung Eun Kim; Won Kyoung Cho; Min Ho Jung; Byung Kyu Suh (Korean Society of Pediatric Endocrinology, 2016)
Cystinosis is a rare disease characterized by abnormal lysosomal cystine accumulation of cystine due to impaired lysosomal transport. We previously reported the first case of cystinosis in Korea in a 12-year-old boy with short stature, general weakness, and photophobia. The diagnosis was confirmed based on ophthalmic findings and biochemical analyses (serum leukocyte cystine measurement). Major endocrine manifestations at diagnosis included hypothyroidism, growth retardation, and hypogonadism. Despite oral cysteamine administration and renal replacement therapy, multiple complications including both endocrine and nonendocrine disorders developed during and after adolescence. In this report, we review the presenting features and factors related to the long-term complications in a patient with cystinosis.